(untitled) (Texas Journal of Medical Science, 2023)
To date, despite various newly developed methods of surgical treatment for purulent liver diseases, the frequency of purulent complications and mortality remains high. In this study, the results of treatment for 31 patients with liver abscesses who underwent minimally invasive surgical interventions were analyzed. Along with drainage of the purulent cavity of the liver, patients simultaneously underwent long-term catheter therapy with catheterization of their own renal artery. Using this strategy, we managed to achieve favorable clinical outcomes in a short time.